STRATEGI PEMBELAJARAN INKLUSIF BAGI SISWA TUNA DAKSA : STUDI KASUS DI SDN 2 GEMPOLREJO - Budi Astuti; Liftiah; Ali Formen (STKIP Subang, 2026)
This study aims to analyze the implementation of inclusive learning strategies for students with physical disabilities (tuna daksa) in elementary schools, particularly at SDN 2 Gempolrejo. The research is motivated by the challenges faced by teachers in accommodating diverse learning needs in inclusive classrooms. This study employs a qualitative case study approach involving classroom observations, interviews with teachers, and document analysis. The results indicate that teachers have made efforts to adapt instructional methods through differentiated instruction, use of assistive learning media, and flexible classroom management. However, several obstacles were identified, including limited teacher competence in special education, lack of supporting facilities, and minimal parental involvement. Despite these challenges, the implementation of inclusive practices has shown positive impacts on students’ participation and learning motivation. The study concludes that effective inclusive education requires collaborative support among teachers, schools, and stakeholders, as well as continuous professional development for educators. These findings provide practical implications for improving inclusive learning strategies in elementary education settings.